Aluminum-based MOF (Metal Organic Framework) mixed matrix membrane based on perfluoroalcohol modification as well as preparation method and application of aluminum-based MOF mixed matrix membrane
Through the perfluoroethanol-modified aluminum-based MOF nanocrystals, the shortcomings in the interfacial compatibility and separation performance of the aluminum-based MOF hybrid matrix membrane were solved, and an aluminum-based MOF hybrid matrix membrane with excellent molecular sieving ability and structural stability was prepared, achieving efficient separation of a variety of gases and liquids.
Patent Information
- Application Number
- CN202411581015.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing aluminum-based MOF hybrid matrix membranes have shortcomings in interface compatibility, mechanical strength and separation performance, making it difficult to achieve efficient separation of gases and liquids such as carbon dioxide/methane, ethylene/ethane and alkane isomers.
By modifying the aluminum-based MOF nanocrystals with perfluoroethanol, changing their surface properties, making them sufficiently hydrophobic and better compatible with the polymer matrix, an aluminum-based MOF hybrid matrix membrane with excellent molecular sieving capabilities and structural stability was prepared.
It achieves good compatibility between aluminum-based MOF and polymer matrix, improves the molecular sieving ability and structural stability of the membrane, and can efficiently separate systems such as carbon dioxide/methane, ethylene/ethane and alkane isomers.
Smart Images

Figure CN119524655A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically relates to an aluminum-based MOF mixed matrix membrane modified by perfluoroalcohol, and a preparation method and application thereof. Background Art
[0002] Aluminum-based MOFs have attracted much attention due to their diverse structures, high structural stability, low preparation cost, and simple scalable synthesis. These significant advantages make them promising membrane materials for potential industrial applications. The preparation of mixed matrix membranes by blending aluminum-based MOFs with polymers as fillers has become a hot topic in the development of high-performance membranes. However, since aluminum-based MOF crystals usually have strong rigidity and high surface energy, they often show poor interfacial bonding when directly combined with polymer materials, resulting in poor interfacial compatibility of the membrane, insufficient mechanical strength, and unsatisfactory separation performance.
[0003] To address this problem, coating MOFs with coatings or surfactants is the mainstream solution to enhance the interfacial compatibility of MOFs and polymers. However, the thickness and uniformity of the coatings are usually difficult to control, and the coatings may fall off or degrade over time or during use, affecting the long-term stability and performance of the membrane. Although the introduction of functional groups on the aluminum-based MOF framework by crystal engineering can also improve the interfacial compatibility of MOFs, the selectivity and reactivity of different groups may be limited, resulting in uneven surface modification, or in some cases, inducing side reactions, thereby affecting the overall performance of the membrane. In general, it is still challenging for existing preparation processes to obtain aluminum-based MOF mixed matrix membranes with high filling content and no interfacial defects. Summary of the invention
[0004] In view of the shortcomings and deficiencies of the prior art, the object of the present invention is to provide an aluminum-based MOF mixed matrix membrane, in which the aluminum-based MOF and the matrix material have good compatibility, the membrane has excellent molecular sieving ability and structural stability, and can achieve efficient separation of systems such as carbon dioxide / methane, ethylene / ethane and alkane isomers.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] An aluminum-based MOF mixed matrix membrane comprises a polymer and modified aluminum-based MOF nanocrystals. The modified aluminum-based MOF nanocrystals are obtained by modifying the aluminum-based MOF nanocrystals with perfluoroalcohol.
[0007] In some embodiments, the perfluoroalcohol is selected from a combination of one or more of perfluorooctanol, perfluoroheptanol, perfluoropentanol and perfluorooctylethanol.
[0008] In some embodiments, the mass of the modified aluminum-based MOF nanocrystals accounts for 5% to 40% of the total mass of the modified aluminum-based MOF nanocrystals and the polymer.
[0009] In some embodiments, the aluminum-based MOF is selected from CAU-23, CAU-10-NH 2 、KMF-1、MIL-53-NH 2 and a combination of one or more of MOF-303.
[0010] In some embodiments, the water contact angle of the modified aluminum-based MOF nanocrystals is 90 to 140°.
[0011] In some embodiments, the modified aluminum-based MOF nanocrystals are prepared by a preparation method comprising the following steps: dispersing the aluminum-based MOF nanocrystals in a solvent to obtain a dispersion; adding the perfluoroalcohol to the dispersion, mixing, centrifuging, and drying to obtain the modified aluminum-based MOF nanocrystals.
[0012] In some embodiments, the mass fraction of the perfluoroalcohol in the dispersion is 0.1% to 2.5%.
[0013] In some embodiments, the polymer is selected from polyimide and / or microporous polymer PIM-1, and the microporous polymer PIM-1 is prepared by polymerization of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane (TTSBI) and 2,3,5,6-tetrafluoroterephthalonitrile (TFTDN).
[0014] In some embodiments, the polyimide is prepared by polycondensation and dehydration of 4,4′-(hexafluoroisopropyl)phthalic anhydride (6FDA) and 2,4,6-trimethyl-1,3-phenylenediamine (DAM).
[0015] In the prior art, conventional mixed matrix membranes usually have problems such as poor interface compatibility and blockage of MOF membrane crystal channels. The inventors of this application have found through research that the aluminum-based MOF nanocrystals are first modified with perfluoroalcohols. Since perfluoroalcohols have strong hydrophobicity, the modified aluminum-based MOF nanocrystals can be made hydrophobic, so that the aluminum-based MOF nanocrystals can significantly change the surface characteristics of the aluminum-based MOF nanocrystals while maintaining the crystallinity and pore structure of the aluminum-based MOF, so that the aluminum-based MOF nanocrystals have sufficient hydrophobicity. In addition, since perfluoroalcohols can undergo esterification reaction with the carboxyl groups on the surface of the aluminum-based MOF, the modified layer is highly uniform and stable, thereby significantly improving the dispersibility of the aluminum-based MOF in the casting solution of the mixed matrix membrane, and then significantly improving the compatibility between the aluminum-based MOF nanocrystals and the polymer matrix. The aluminum-based MOF mixed matrix membrane thus obtained has excellent molecular sieving ability and structural stability, and can achieve efficient separation of systems such as carbon dioxide / methane, ethylene / ethane and alkane isomers.
[0016] In some embodiments, the aluminum-based MOF mixed matrix membrane is prepared by casting a casting solution including the polymer, modified aluminum-based MOF nanocrystals and an organic solvent.
[0017] The present invention also provides a method for preparing the above-mentioned aluminum-based MOF mixed matrix membrane, which comprises the following steps: dispersing the aluminum-based MOF nanocrystals in a solvent to obtain a dispersion; adding the perfluoroalcohol to the dispersion, mixing, centrifuging, and drying to obtain the modified aluminum-based MOF nanocrystals; mixing the polymer, the modified aluminum-based MOF nanocrystals, and an organic solvent to obtain a casting liquid; and casting the casting liquid to obtain the aluminum-based MOF mixed matrix membrane.
[0018] In some embodiments, the solvent is selected from a combination of one or more of ethanol, methanol, and chloroform.
[0019] In some embodiments, the mass fraction of the perfluoroalcohol in the dispersion is 0.1% to 2.5%.
[0020] In some embodiments, the mass fraction of the aluminum-based MOF nanocrystals in the dispersion is 0.5% to 5%.
[0021] In some embodiments, the organic solvent is selected from a combination of one or more of N,N-dimethylformamide, chloroform and dichloromethane.
[0022] In some embodiments, the mass fraction of the polymer in the casting solution is 1.0% to 5.0%.
[0023] In some embodiments, the preparation method includes the following steps: dispersing the aluminum-based MOF nanocrystals in a solvent to obtain a dispersion; adding the perfluoroalcohol to the dispersion, stirring and mixing, centrifuging, washing, and vacuum drying to obtain the modified aluminum-based MOF nanocrystals; mixing the polymer, modified aluminum-based MOF nanocrystals, and an organic solvent to obtain a casting liquid; vacuum degassing the casting liquid, transferring it to a mold, evaporating the solvent at room temperature, and vacuum drying to obtain the aluminum-based MOF mixed matrix membrane.
[0024] In some embodiments, the stirring and mixing time is 5 to 12 hours.
[0025] In some embodiments, when preparing the modified aluminum-based MOF nanocrystals, the vacuum drying temperature is 60 to 80° C., and the vacuum drying time is 6 to 12 hours.
[0026] In some embodiments, the time for evaporating the solvent is 12 to 48 hours.
[0027] In some embodiments, when preparing the aluminum-based MOF mixed matrix membrane, the vacuum drying temperature is 60 to 80° C., and the vacuum drying time is 12 to 24 hours.
[0028] The present invention also provides use of the aluminum-based MOF mixed matrix membrane for gas or liquid separation.
[0029] Furthermore, the gas is selected from carbon dioxide / methane, ethylene / ethane; and the liquid is hexane isomers.
[0030] Furthermore, the hexane isomers may be a ternary mixture of n-hexane, 3-methylpentane and 2,2-dimethylbutane.
[0031] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0032] The present invention firstly uses perfluoroalcohol to modify aluminum-based MOF nanocrystals. Since perfluoroalcohol has strong hydrophobicity, the modified aluminum-based MOF nanocrystals can be made hydrophobic, so that the aluminum-based MOF nanocrystals can significantly change the surface characteristics of the aluminum-based MOF nanocrystals under the premise of maintaining the crystallinity and pore structure of the aluminum-based MOF, so that the aluminum-based MOF nanocrystals have sufficient hydrophobicity. In addition, since perfluoroalcohol can undergo esterification reaction with the carboxyl group on the surface of the aluminum-based MOF, the modified layer is highly uniform and stable, thereby significantly improving the dispersibility of the aluminum-based MOF in the casting solution of the mixed matrix membrane, and then significantly improving the compatibility between the aluminum-based MOF nanocrystals and the polymer matrix. The aluminum-based MOF mixed matrix membrane thus obtained has excellent molecular sieving ability and structural stability, and can achieve efficient separation of systems such as carbon dioxide / methane, ethylene / ethane and alkane isomers. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The water contact angle of CAU-23 nanocrystals modified with different amounts of perfluorooctanol;
[0034] Figure 2 XRD patterns of CAU-23 nanocrystals modified with different amounts of perfluorooctanol;
[0035] Figure 3 Surface and cross-sectional SEM images of the aluminum-based MOF mixed matrix membrane prepared in Example 1;
[0036] Figure 4 AFM image of the aluminum-based MOF mixed matrix membrane prepared in Example 1;
[0037] Figure 5 This is the cross-sectional EDS mapping image of the aluminum-based MOF mixed matrix membrane prepared in Example 2;
[0038] Figure 6 Surface and cross-sectional SEM images of the aluminum-based MOF mixed matrix membrane prepared in Comparative Example 1. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention, but the present invention is not limited to the scope of the examples.
[0040] Example 1
[0041] This embodiment provides an aluminum-based MOF mixed matrix membrane, and the preparation steps thereof are as follows:
[0042] 1. Perfluoroalcohol modification
[0043] 0.5 g of CAU-23 nanocrystals were dispersed in 50 mL of ethanol solution to form a nanocrystal suspension. Subsequently, a certain amount of perfluorooctanol was weighed and added to the CAU-23 nanocrystal ethanol dispersion. After stirring at room temperature for 24 h, the mixture was centrifuged and washed three times with methanol, and finally dried in a vacuum drying oven at 60 ° C for 12 h to obtain perfluorooctanol-modified CAU-23 nanocrystals.
[0044] At the same time, the surface hydrophobicity of CAU-23 nanocrystals can be simply changed by changing the mass percentage concentration of perfluorooctanol in the CAU-23 ethanol dispersion. Figure 1The static water contact angle data of CAU-23 nanocrystals modified at different perfluorooctanol addition amounts (mass percentage in the dispersion) are presented. The results show that the water contact angle of CAU-23 nanocrystals increases monotonically with the increase in the amount of perfluorooctanol added. At a concentration of 1.0wt%, the surface properties of CAU-23 change from hydrophilic to hydrophobic, which reflects the powerful interfacial energy regulation ability of perfluoroalcohols.
[0045] Figure 2 and Figure 3 The XRD patterns and SEM images of the prepared perfluorooctanol-modified CAU-23 nanocrystals are shown, indicating that the modification steps have no effect on the crystal structure integrity and crystal morphology characteristics of CAU-23 nanocrystals. Table 1 shows the XRD patterns and SEM images of the prepared perfluorooctanol-modified CAU-23 nanocrystals at 77K based on N 2 The specific surface area and pore volume data of perfluorooctanol-modified CAU-23 nanocrystals obtained by adsorption-desorption isotherms. It can be seen that when the mass concentration of perfluorooctanol in the dispersion is below 2wt.%, the specific surface area and pore volume of the modified CAU-23 are only slightly reduced, while the average pore size remains basically unchanged, while at 3wt.%, the specific surface area and pore volume are significantly reduced, that is, the porosity of CAU-23 is greatly affected.
[0046] Table 1 Pore structure information of CAU-23 nanocrystals modified with different perfluorooctanol concentrations
[0047]
[0048] 2. Preparation of PIM-1:
[0049] Take 7.5g of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane TTSBI and dissolve it in 200mL of methanol. Transfer the solution to a rotary evaporator and install a rotary evaporator. Use a speed of 220r / min and vacuum distill at 45℃ until the solution remains 50mL. Then add 100mL of dichloromethane to the system and precipitate overnight. Collect the precipitate at 60℃ and vacuum dry it for storage.
[0050] Take 4.5 g of 2,3,5,6-tetrafluoroterephthalonitrile TFTDN and dissolve it in 75 mL of acetone. Add deionized water dropwise until it is completely precipitated. Dry it under vacuum at 60°C and store it.
[0051] Grind the crude potassium carbonate for 30 min, put it into a glass bottle, vacuum dry it at 130°C for 24 h, and store it in a dry state to obtain fine potassium carbonate.
[0052] 3.4 g of purified TTSBI and 2.0 g of purified TFTDN were placed in a 250 mL three-necked flask, and 70 mL of N,N-dimethylacetamide was added and stirred until the solution was clear; 4.15 g of fine potassium carbonate was added to the solution and the device was moved to a nitrogen environment, and the reaction was stirred at 65 ° C for 72 h. The yellow bright solution after the reaction was poured into a deionized hydrochloric acid solution (14 wt.%) at 80 ° C and stirred at a constant temperature for 12 h to remove potassium carbonate. After filtration, it was dried, and the dried sample was dissolved in 100 mL of chloroform, and then transferred to methanol for precipitation by negative pressure filtration. The precipitated product was vacuum dried for 24 h. Finally, it was washed with 100 mL of 4-dioxane, 100 mL of acetone, 100 mL of deionized water and excess methanol to remove low molecular weight PIM-1 and unreacted raw materials. After washing, it was vacuum dried at 60 ° C for 24 h to obtain a PIM-1 sample for film formation. The molecular weight of the synthesized PIM-1 was 170,000 g / mol.
[0053] 3. Preparation of membrane
[0054] The perfluorooctanol-modified CAU-23 / PIM-1 mixed matrix membrane was prepared by solution casting. 0.2 g of perfluorooctanol-modified CAU-23 nanocrystals (perfluorooctanol is 1 wt.% concentration) were dispersed in 6 g of chloroform, and ultrasonic treatment was performed for 20 min to obtain a CAU-23 nanocrystal dispersion. 0.3 g of the PIM-1 sample prepared above was dissolved in 10 g of chloroform to obtain a PIM-1 casting solution, and the CAU-23 nanocrystal dispersion prepared above was added to mix to prepare a mixed matrix membrane casting solution in which nanocrystals accounted for 40% of the total mass of the mixed matrix membrane and the polymer, and degassed in an ultrasonic machine for 10 min. After degashing, the casting solution was transferred to a mold, and the mold was placed on a horizontally corrected flat plate. The solvent chloroform was slowly evaporated at room temperature for 48 h, and then vacuum dried at 60° C. for 24 h to form a film. Finally, the mixed matrix membrane was cut into small pieces of membrane with a diameter of about 3 cm using a carving knife mold for performance testing. Pure PIM-1 membranes were prepared using the same method without the addition of CAU-23 nanocrystals.
[0055] Figures 3 to 5 The surface / cross-sectional SEM images, surface AFM images and cross-sectional EDSmapping images of the obtained mixed matrix membrane were respectively shown. The results showed that the mixed matrix membrane was dense and free of interface defects, and the perfluorooctanol-modified CAU-23 nanocrystals were uniformly dispersed in the PIM-1 matrix without agglomeration. The membrane showed excellent separation performance for the ternary mixture system of hexane isomers, with a separation factor of ~4.87 for (n-hexane + 3-methylpentane) / 2,2-dimethylbutane and a total permeation flux of ~1500 g·m for (n-hexane + 3-methylpentane). -2 ·h -1, and there was no attenuation of separation performance after continuous operation for 100 hours. In contrast, the separation selectivity of the prepared mixed matrix membrane was improved by 3 times compared with the pure phase PIM-1, and exceeded most of the reported membrane materials, showing the prospect of practical application.
[0056] Example 2
[0057] This embodiment provides an aluminum-based MOF mixed matrix membrane, and the preparation steps thereof are as follows:
[0058] 1. Perfluoroalcohol modification
[0059] The preparation of CAU-23 nanocrystals modified with 1 wt.% perfluorooctanol was the same as in Example 1.
[0060] 2. Preparation of 6FDA-DAM:
[0061] Weigh a certain amount of diamine DAM and dissolve it in N,N-dimethylacetamide to prepare a 20wt.% solution, and then add dianhydride FDA. The mixed solution is reacted at 5°C and nitrogen protection for 24 hours to generate a polyamic acid solution. Then, acetic anhydride and triethanolamine are added to the above solution in a molar ratio of 4:1, and reacted at room temperature for 24 hours to generate polyimide from polyamide. Finally, the solution is poured into enough methanol to precipitate the polymer, and vacuum dried at 150°C for 12 hours. The molecular weight of the synthesized 6FDA-DAM is 180,000g / mol.
[0062] 3. Preparation of membrane
[0063] The perfluorooctanol-modified CAU-23 / 6FDA-DAM mixed matrix membrane was prepared by the solution casting method of Example 1.
[0064] The 1wt.% concentration of perfluorooctanol-modified CAU-23 nanocrystals was dispersed in chloroform and ultrasonically treated for 20min to obtain a 10mg / mL CAU-23 nanocrystal dispersion. 6FDA-DAM was first dried overnight at 150°C under vacuum to remove residual moisture before use. 0.42g of 6FDA-DAM was weighed and dissolved in 4.1mL of chloroform and stirred for 3h. Subsequently, a certain amount of the aforementioned perfluorooctanol-modified CAU-23 nanocrystal dispersion was added to the 6FDA-DAM solution, and stirring was continued overnight to uniformly disperse the CAU-23 nanocrystals in the solution to obtain a 6FDA-DAM mixed matrix membrane casting solution in which the nanocrystals accounted for 40% of the total mass of the polymer. The obtained suspension was poured into a glass plate on a flat surface, and the plate was then placed in a dryer pre-saturated with chloroform vapor. The dryer was designed with a small outlet to reduce the solvent evaporation rate. After slowly evaporating the solvent for 3 days, a dense and defect-free mixed matrix membrane was obtained. The film was dried in a vacuum oven at 180°C for 24 hours to remove the residual solvent, and a dense CAU-23 / 6FDA-DAM mixed matrix film with no interface defects was obtained. Finally, the mixed matrix film was cut into small pieces with a diameter of about 3 cm using a carving mold for performance testing. Pure 6FDA-DAM film was prepared using the same method without adding CAU-23 nanocrystals.
[0065] The mixed matrix membrane was installed in a membrane module for the separation of an equimolar ethylene / ethane binary mixture. The membrane had a separation selectivity of 3.7 for ethylene / ethane and an ethylene permeation flux of 135 Barrer. Compared with pure 6FDA-DAM, both the ethylene / ethane separation selectivity and the ethylene permeation flux were doubled, indicating that the prepared mixed matrix membrane had no defects at the interface and could give full play to the advantages of CAU-23 nanocrystal channels, and had good application prospects.
[0066] Example 3
[0067] This embodiment provides an aluminum-based MOF mixed matrix membrane, and its preparation steps are basically the same as those in Example 1, except that: 1 wt.% concentration of perfluorooctylethanol is used to modify the surface of CAU-23 nanocrystals, and the rest is the same as in Example 1.
[0068] The obtained membrane also exhibited excellent separation performance for the ternary mixture of hexane isomers, with a separation factor of ~4.43 for (n-hexane + 3-methylpentane) / 2,2-dimethylbutane and a total permeation flux of ~1396 g·m for (n-hexane + 3-methylpentane). -2 ·h -1 , and there is no attenuation of separation performance after continuous operation for 100h.
[0069] Example 4
[0070] This embodiment provides an aluminum-based MOF mixed matrix membrane, and the preparation steps are basically the same as those in Example 2, except that the CAU-23 nanocrystals are replaced by CAU-10-NH 2 The obtained membrane has excellent separation performance for equimolar carbon dioxide / methane binary mixture, the separation selectivity of carbon dioxide / methane is up to 34, and the ethylene permeation flux of the membrane is 650 Barrer.
[0071] Comparative Example 1
[0072] The method is basically the same as Example 1, except that the CAU-23 nanocrystals are not modified with perfluorooctanol. The SEM image of the obtained membrane is as follows: Figure 6 As shown, it can be seen that the membrane exhibits obvious interface defects and particle agglomeration, resulting in the prepared mixed matrix membrane having no hexane isomer separation ability. The separation factor for (n-hexane + 3-methylpentane) / 2,2-dimethylbutane is only 1.27, which is lower than 1.56 of the pure PIM-1 membrane.
[0073] Comparative Example 2
[0074] The method is basically the same as Example 1, except that the concentration of perfluorooctanol in the dispersion is adjusted to 3 wt.%. As shown in Table 1, as the concentration of perfluorooctanol increases to 3 wt.%, it has a greater impact on the porosity of CAU-23 (Table 1), resulting in a significant decrease in the permeation flux of the prepared mixed matrix membrane, with the total permeation flux to (n-hexane + 3-methylpentane) being only 756 g·m -2 ·h -1 , the separation factor for (n-hexane + 3-methylpentane) / 2,2-dimethylbutane is ~2.43.
[0075] Comparative Example 3
[0076] The method is basically the same as Example 2, except that the CAU-23 nanocrystals are not modified with perfluorooctanol. The particles in the obtained membrane are unevenly dispersed and agglomerated in large quantities, resulting in the prepared mixed matrix membrane not having the ethylene / ethane separation capability, and the ethylene / ethane separation selectivity is only 1.32.
[0077] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. An aluminum-based MOF mixed matrix membrane, characterized in that: The aluminum-based MOF mixed matrix membrane comprises a polymer and modified aluminum-based MOF nanocrystals, and the modified aluminum-based MOF nanocrystals are obtained by modifying the aluminum-based MOF nanocrystals with perfluoroalcohol.
2. The aluminum-based MOF mixed matrix membrane according to claim 1, characterized in that: The perfluoroalcohol is selected from one or more combinations of perfluorooctanol, perfluoroheptanol, perfluoropentanol and perfluorooctylethanol.
3. The aluminum-based MOF mixed matrix membrane according to claim 1, characterized in that: The mass of the modified aluminum-based MOF nanocrystals accounts for 5% to 40% of the total mass of the modified aluminum-based MOF nanocrystals and the polymer.
4. The aluminum-based MOF mixed matrix membrane according to claim 1, characterized in that: The aluminum-based MOF is selected from a combination of one or more of CAU-23, CAU-10-NH2, KMF-1, MIL-53-NH2 and MOF-303; and / or the water contact angle of the modified aluminum-based MOF nanocrystals is 90 to 140°.
5. The aluminum-based MOF mixed matrix membrane according to claim 1, characterized in that: The modified aluminum-based MOF nanocrystals are prepared by a preparation method comprising the following steps: dispersing the aluminum-based MOF nanocrystals in a solvent to obtain a dispersion; adding the perfluoroalcohol to the dispersion, mixing, centrifuging, and drying to obtain the modified aluminum-based MOF nanocrystals; preferably, the mass fraction of the perfluoroalcohol in the dispersion is 0.1% to 2.5%.
6. The aluminum-based MOF mixed matrix membrane according to claim 1, characterized in that: The polymer is selected from polyimide and / or microporous polymer PIM-1, and the microporous polymer PIM-1 is prepared by polymerizing 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane and 2,3,5,6-tetrafluoroterephthalonitrile.
7. The aluminum-based MOF mixed matrix membrane according to claim 6, characterized in that: The polyimide is prepared by polycondensation and dehydration of 4,4′-(hexafluoroisopropyl)diphthalic anhydride and 2,4,6-trimethyl-1,3-phenylenediamine.
8. A method for preparing the aluminum-based MOF mixed matrix membrane according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: dispersing the aluminum-based MOF nanocrystals in a solvent to obtain a dispersion; adding the perfluoroalcohol to the dispersion, mixing, centrifuging, and drying to obtain the modified aluminum-based MOF nanocrystals; mixing the polymer, the modified aluminum-based MOF nanocrystals, and an organic solvent to obtain a casting liquid; and casting the casting liquid to obtain the aluminum-based MOF mixed matrix membrane.
9. The method for preparing an aluminum-based MOF mixed matrix membrane according to claim 8, characterized in that: The solvent is selected from one or more combinations of ethanol, methanol, and chloroform; and / or the mass fraction of the perfluoroalcohol in the dispersion is 0.1% to 2.5%; and / or the mass fraction of the aluminum-based MOF nanocrystals in the dispersion is 0.5% to 5%.
10. The method for preparing an aluminum-based MOF mixed matrix membrane according to claim 8, characterized in that: The organic solvent is selected from a combination of one or more of N,N-dimethylformamide, chloroform and dichloromethane; and / or the mass fraction of the polymer in the casting solution is 1.0% to 5.0%.
11. The method for preparing an aluminum-based MOF mixed matrix membrane according to claim 8, characterized in that: The preparation method comprises the following steps: dispersing the aluminum-based MOF nanocrystals in a solvent to obtain a dispersion; adding the perfluoroalcohol to the dispersion, stirring and mixing, centrifuging, washing, and vacuum drying to obtain the modified aluminum-based MOF nanocrystals; mixing the polymer, the modified aluminum-based MOF nanocrystals, and an organic solvent to obtain a casting liquid; vacuum degassing the casting liquid, transferring it to a mold, evaporating the solvent at room temperature, and vacuum drying to obtain the aluminum-based MOF mixed matrix membrane.
12. Use of the aluminum-based MOF mixed matrix membrane according to any one of claims 1 to 7 for gas or liquid separation.
13. The use according to claim 12, characterized in that: The gas is selected from carbon dioxide / methane, ethylene / ethane; and the liquid is hexane isomers.
Citation Information
Patent Citations
Dehydration method of organic raw material liquid
CN116710191A
In-situ MOF stereocomplex polylactic acid micro / nano fiber self-powered filter membrane and preparation method thereof
CN116726729A
MOFs (Metal-Organic Frameworks) modified nano-composite fiber membrane for filtering white blood cells as well as preparation method and application thereof
CN118320635A
Method for Preparing Fluorine-Based Polymer, Fluorine-Based Polymer, and Polymer Membrane Comprising the Same
KR102353641B1
Gas Separation Membrane
US20090301307A1
Cited By
Super-hydrophobic carbon dioxide selective permeable membrane as well as preparation method and application thereof
CN122399586A